Factors that influence employee’s job satisfaction in service sector area MITC Complex / Nur Amirah Che Mud - Che Mud, Nur Amirah (Faculty of Business and Management, 2018)
This study aims to examine the factors that influence employee’s job satisfaction in service sector area MITC Complex. Employee’s job satisfaction is very important for organization especially in service sector. It involved people’s feeling toward their jobs. . When a person responds that he has high job satisfaction, it shows that he really loves his job, feels better about it and values his job dignity. This study includes the objectives as follows, to study the relationship between compensation, work environment, job stress, leadership styles towards employee’s job satisfaction and to identify the most influence factors compensation, work environment, job stress, leadership styles between employee’s job satisfactions. In order to achieve all these two objectives, the quantitative study methods were used and the data were gathered by distributing structured questionnaire to all the employees at MITC Complex which are Melaka ICT Holdings Sdn Bhd and Malacca International Trade Centre. The questionnaire was measured by using Likert scale to collect data from the respondents and its reliability is considered high. Descriptive analysis was used to summarize all data in order to determine the respondents answer. Besides, Person Correlation Analysis was used to determine whether there is a relationship between independent variables and dependent variable. Other than that, Multiple Regression analysis is also used to examine the relationship between compensation, work environment, job stress, leadership style and job satisfaction of the employees. This study was concluded with conclusion, recommendations from the findings of this study and future research.